Transactional VS. Transformational Leadership in Healthcare: Evaluating Their Influence on Operational Efficiency and Quality of Care - Anand , Dr.J.; Sentamilselvan , Dr.K.; Selvaranee, Dr.J. Kavitha; Nihlani , Dr. Ankita; Sachdeva , Dr. Lalit (International Journal of Accounting and Economics Studies, 2025)
Leadership sits at the heart of every successful hospital or clinic, shaping how smoothly the organization runs and how patients experience care. This study looks at two well-known styles-transformational and transactional- and examines how each can spark staff enthusiasm, boost performance, and lift patient outcomes. People who follow a transactional approach create clear rules, reward effort, and track results constantly, a formula that often lines up with tight operations and predictable processes. Transformational leaders, on the other hand, trade routine for vision; they encourage fresh ideas, keep growth in sight, and build a culture where each team member thinks first of the patient. To weigh the pros and cons of these styles, the team mixed surveys, interviews, and hard metrics, then linked the scores to key targets such as patient satisfaction, staff output, and clinical quality. Through a blend of real-world case stories and controlled data, the research sketches a roadmap for marrying efficiency with excellent care in ever-changing health settings. The results then point managers toward concrete training and support actions so that workplaces can become leaner without losing the human touch patients deserve.